2010
DOI: 10.2147/opth.s8892
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of monocular surgery for horizontal strabismus in Hyderabad

Abstract: Background and objectiveSquint surgery is frequently performed successfully in Hyderabad. However, no study in any detail has been performed on the outcome of monocular surgery for horizontal squint in the region. This study aims to determine the results of monocular surgery for horizontal trabismus.DesignRetrospective/observational study.Subjects and methodsThe study was conducted on patients aged under 45 years, presenting with horizontal strabismus and undergoing monocular squint surgery. Anterior segment s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Many define satisfactory alignment as within 10 PD of orthotropia, [13,23,27] while others extend the criteria to within 15 PD [28,29]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many define satisfactory alignment as within 10 PD of orthotropia, [13,23,27] while others extend the criteria to within 15 PD [28,29]. …”
Section: Discussionmentioning
confidence: 99%
“…The pre-operative deviations of 60 PD or less illustrated success with the unilateral recess/resect procedure, but they stated difficulty in visually aligning the eyes by operating only on one eye because of larger deviations of more than 60 PD. Thus according to them at this stage, clinical circumstances for a second surgery on the fixing eye or binocular squint surgery concerning more than two horizontal rectus muscles is the main and extensive used clinical procedure [29]. Jeoung et.al, in his comparative study found the significantly higher surgical success in patients with the unilateral recess/resect procedure than those having bilateral lateral rectus recession.…”
Section: Discussionmentioning
confidence: 99%
“…For these cases, a second surgery was required with more than two muscle procedure. 19 In our study, one patient with exotropia > 60 PD required second surgery.…”
Section: Discussionmentioning
confidence: 59%
“…The favourable age for operation is when the child can be assessed for orthoptic correction and also when the functional and cosmetic symptoms become too apparent. [15][16][17][18] According to the study conducted by Junejo SA et al, 19 the desired postop effect was seen with preoperative deviation of < 60 PD. With deviation > 60 PD, there was difficulty in aligning the eyes with operation only on one eye.…”
Section: Discussionmentioning
confidence: 99%